2022
DOI: 10.1007/s10877-022-00911-4
|View full text |Cite
|
Sign up to set email alerts
|

New guidelines for research in airway device evaluation: time for an updated approach (ADEPT-2) to the Difficult Airway Society’s ‘ADEPT’ strategy?

Abstract: In this article we present the learning from a clinical study of airway device evaluation, conducted under the framework of the Difficult Airway Society (DAS, UK) ‘ADEPT’ (airway device evaluation project team) strategy. We recommend a change in emphasis from small scale randomised controlled trials conducted as research, to larger-scale observational, post-marketing evaluation audits as a way of obtaining more meaningful information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Ours is not the first reported trial of the LMA Protector. Sng et al's description in 2017 [22] was in fact contemporaneous with the planning of our own trial, and the delays we then encountered are described in the accompanying article [9], and since then there exist over a dozen reports, including description of its use in different patient positions, emergency and elective settings, and for facilitating use of fibrescopy [13,23,24]. However, whereas most of these are individual case series or relatively small (but albeit appropriately statistically powered) randomised trials, ours is arguably the first study of a diverse patient cohort in real world settings.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Ours is not the first reported trial of the LMA Protector. Sng et al's description in 2017 [22] was in fact contemporaneous with the planning of our own trial, and the delays we then encountered are described in the accompanying article [9], and since then there exist over a dozen reports, including description of its use in different patient positions, emergency and elective settings, and for facilitating use of fibrescopy [13,23,24]. However, whereas most of these are individual case series or relatively small (but albeit appropriately statistically powered) randomised trials, ours is arguably the first study of a diverse patient cohort in real world settings.…”
Section: Discussionmentioning
confidence: 86%
“…This proliferation of SADs, coupled with a recognised lack of clinical evidence supporting use of the new devises before they were brought to market led the Difficult Airway Society (DAS) to develop guidance (termed ADEPT after the Airway Device Project Evaluation Team) as a framework under which clinical studies could be facilitated [8]. It was under this framework (described further in an accompanying article [9]) that we undertook a prospective observational cohort study of the LMA® Protector™ to investigate its clinical performance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This study followed the recommendations suggested by ADEPT [9] and ADEPT-2 [10] initiatives and, in a large sample, focused on the clinically important primary outcome, the total success rate of the i-gel Plus insertion. The interim results of this trial showed that the total success rate of the device insertion is reasonably high in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…9 The first formal trial under this program was recently published, 10 and moreover, updated recommendations (ADEPT-2) have been proposed. 11 The performance of SGDs, which can range from easy to problematic, depends on patient factors, the anesthetic plan (including urgency of any intervention) and the SGD design (including dimensions and material). Some SGDs are bulkier than others.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…9 The first formal trial under this program was recently published, 10 and moreover, updated recommendations (ADEPT-2) have been proposed. 11…”
mentioning
confidence: 99%